Analysis of factors affecting decision to use Thai Airline service using Nested Logit Model - Piyoros Youngyoodee (International Journal of Supply Chain Management, 2017)
Abstract: These research studies as analysis of factors influencing the decision to use the service by Thai Airways by use Nested Logit Model. By the objective was to study the composition and other factors that affect the decision of passenger for use to study the characteristic in services provided by the Thai Airline. This research has study to format of the options studied by the passenger's choice of decision making level variables as the result is a variable in the Nested Logit Model. Were determining relationship of each variable to consider when deciding of passenger. The data used in this study are primary data obtained from questionnaires collected from passengers using the airline's 400 number. The study indicated to factorss influence the decision to use Thai Airways factors include revenue objective factors journey. The factor in travel time is direct cost of passenger. Therefore Thai Airways Should to low costs and lower fares to suit the needs of passengers.